Small Ruminant Breeding Plans for Smallholder Systems - Luis Iniguez (Indonesian Center for Animal Research and Development, 2017)
The transfer of animal genetic improvement strategies in the environments of resource-poor smallholder producers in developing countries has not been successful. Therefore, the access by farmers to sources of animals with high genetic potential is difficult or just not possible. As producers improve or intensify their systems to capture market opportunities, this access need is accentuated. This paper reviews identified constraints to the transfer of breeding plans, the need for a new approach, and the lessons learned in applying a better-targeted approach. The issues and thoughts were derived from the experience of a working group involving the International Center for Agricultural Research in the Dry Areas; Austrian University of Natural Resources and Life Sciences; Argentinean National Institute of Agriculture Technology; Brazilian Agricultural Research Corporation (Embrapa Goats and Sheep); and National Research Institute for Forestry, Agriculture and Animal Production-Mexico. The transfer of breeding strategies in smallholder systems is not a straightforward task. Contrasting a successful application in commercial livestock production environments, the achievement of the primary objectives in smallholder systems requires a holistic approach beyond pure technical matters. Of all identified aspects with direct incidence in the implementation of breeding plans, the lack of specific national policies coupled with long-term funding to support the improvement of smallholder production systems, and the lack of involvement and participation of the communities emerge as issues that gravitate more to achieve sustainability and meet the objectives of a given breeding plan.